2008
DOI: 10.1007/978-3-7908-2086-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Regional Inequalities in Greece

Abstract: This article examines regional inequalities in Greece, on the basis of σ-convergence and β-convergence analysis and shows that they were reduced in the 1970s and the 1980s. Regression analysis indicates that regional inequalities have a pro-cyclical character, increasing in periods of economic expansion and decreasing in periods of economic recession. It also indicates that the structure of local industry, the process of EU integration, the quality of human capital and the existence of resources suitable for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 43 publications
3
62
0
1
Order By: Relevance
“…Some authors have found evidence that regional disparities tend to behave in a pro‐cyclical manner, that is, increasing in periods of economic expansion and decreasing in periods of slow growth. This pattern has been identified for short‐term growth processes by Petrakos, Rodríguez‐Pose, and Rovolis (2005) for the EU as a whole and by Ioannides and Petrakos (2000) and by Petrakos (2001) for Greece alone. Dewhurst (1998) also detected a pro‐cyclical evolution of disparities in the UK for the period 1984–1993, as did Cuadrado‐Roura, Mancha Navarro, and Garrido Yserte (1998) and Rodríguez‐Pose (2000) between 1985 and 1999 for Spain.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Some authors have found evidence that regional disparities tend to behave in a pro‐cyclical manner, that is, increasing in periods of economic expansion and decreasing in periods of slow growth. This pattern has been identified for short‐term growth processes by Petrakos, Rodríguez‐Pose, and Rovolis (2005) for the EU as a whole and by Ioannides and Petrakos (2000) and by Petrakos (2001) for Greece alone. Dewhurst (1998) also detected a pro‐cyclical evolution of disparities in the UK for the period 1984–1993, as did Cuadrado‐Roura, Mancha Navarro, and Garrido Yserte (1998) and Rodríguez‐Pose (2000) between 1985 and 1999 for Spain.…”
Section: Introductionmentioning
confidence: 57%
“…The reasons for this behavior of rich and poor regions in Greece are related to two factors: the reliance on tourism as the main source of revenue by various dynamic Greek regions and the expansion of industrial activity from Athens to its neighboring regions. Many Greek regions with an intermediate level of development at the beginning of the 1980s—and especially the islands of Crete, the South Aegean, and Ionian islands—have kept their economies relatively open, thanks to their dependence on tourism flows and have, as a consequence, grown faster than other regions more reliant on agriculture or on other types of services (Petrakos and Saratsis 2000). Hence, in Greece, tourism helps to offset the concentration of economic activity in the more developed areas of the country, operating “as a counterbalancing force to the endogenous tendencies of industrial activity to concentrate in selected areas” (Petrakos and Saratsis 2000: 69; see also Ioannides and Petrakos 2000).…”
Section: The Emergence Of Sheltered Economies In the Southern Periphementioning
confidence: 99%
See 2 more Smart Citations
“…The country's presence in the European unification process has shaped its national and regional economic policy orientation. One of the key questions raised by a number of studies is whether the integration course has enhanced regional growth and convergence (Syriopoulos and Asteriou, 1998;Petrakos and Saratsis, 2000;Tsionas, 2002;Michelis et al, 2004;Christopoulos and Tsionas, 2004;Alexiadis andTomkins, 2004, Benos andKaragiannis, 2008). Empirical results reported mixed evidence at both the regional (NUTS 2) and prefecture levels (NUTS 3).…”
Section: Introductionmentioning
confidence: 99%